2021
DOI: 10.1093/braincomms/fcab026
|View full text |Cite|
|
Sign up to set email alerts
|

Hippocampal atrophy is associated with psychotic symptom severity following traumatic brain injury

Abstract: Psychosis is a rare, but particularly serious sequela of traumatic brain injury. However, little is known as to the neurobiological processes that may contribute to its onset. Early evidence suggests that psychotic symptom development after traumatic brain injury may co-occur with hippocampal degeneration, invoking the possibility of a relationship. Particularly regarding the hippocampal head, these degenerative changes may lead to dysregulation in dopaminergic circuits, as is reported in psychoses due to schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…This domain broadly encompasses NPS associated with positive psychotic symptoms. Interestingly, emerging literature has suggested that, in the chronic stages of moderate–severe TBI, progressive hippocampal atrophy may dysregulate amplitude of dopaminergic firing in mesolimbic circuits, increasing risk of positive psychotic symptoms in the years post‐injury 19,46 . After moderate–severe TBI, hippocampal volumetric decrements have been observed and may continue to progress for years after the injury event 47,48 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This domain broadly encompasses NPS associated with positive psychotic symptoms. Interestingly, emerging literature has suggested that, in the chronic stages of moderate–severe TBI, progressive hippocampal atrophy may dysregulate amplitude of dopaminergic firing in mesolimbic circuits, increasing risk of positive psychotic symptoms in the years post‐injury 19,46 . After moderate–severe TBI, hippocampal volumetric decrements have been observed and may continue to progress for years after the injury event 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…19,46 After moderate-severe TBI, hippocampal volumetric decrements have been observed and may continue to progress for years after the injury event. 47,48 In the context of dementia, TBI may introduce vulnerabilities to hippocampal neurodegeneration, such as vascular dysfunction, 49 thereby increasing risk of these NPS by similar mechanisms as have been proposed outside the context of dementia (see Bray et al 19 and Grace 46 ). The present study found that risk of this MBI domain was increased solely in the more severe group and that increased risk appeared to be more pronounced later in dementia progression; while these are in line with this possible explanation, evidence in support of this proposed mechanism is preliminary and further study is required.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations